Biology of Plants - Raven, Peter H.; Evert, Ray Franklin; Eichhorn, Susan E. (New York W.H. Freeman and Company, 2005)
Biology of Plants is especially known for its comprehensive coverage and its magnificent art program. The new edition offers a wealth of new information, especially in the areas of taxonomy, genomics, plant hormones, and Arabidopsis research.
Include Color Illustrations, Glossary and Index.
Keywords: Botany -- Plant ecology -- Plants--Development -- Plant physiology